Money demand and macroeconomic uncertainty - Wolfgang Lemke; Claus Greiber (Deutsche Bundesbank, 2005)
In this study we construct a measure of macroeconomic uncertainty from several observable economic indicators for the euro area. Indicator variables are based on financial market data, such as medium-term returns, loss and volatility measures but also come from surveys that capture business and consumer sentiment. From these we estimate the path of underlying macroeconomic uncertainty using an unobserved components model. Employing cointegration analysis it is demonstrated that the extracted measures of uncertainty help to explain the increase in euro area M3 over the period 2001 to 2004. Similar evidence can be found for US monetary aggregates.
Keywords: E41; 330; Money demand; Macroeconomic Uncertainty; Excess Liquidity; Geldnachfrage; Geldmenge; Konjunktur; Makroökonomischer Einfluß; Schätzung; EU-Staaten; USA